Metabolic engineering approaches for the biosynthesis of antibiotics - Geunsoo Yook; Jiwoo Nam; Yeonseo Jo; Hyunji Yoon; Dongsoo Yang (Microbial Cell Factories)
Abstract Background Antibiotics have been saving countless lives from deadly infectious diseases, which we now often take for granted. However, we are currently witnessing a significant rise in the emergence of multidrug-resistant (MDR) bacteria, making these infections increasingly difficult to treat in hospitals. Main text The discovery and development of new antibiotic has slowed, largely due to reduced profitability, as antibiotics often lose effectiveness quickly as pathogenic bacteria evolve into MDR strains. To address this challenge, metabolic engineering has recently become crucial in developing efficient enzymes and cell factories capable of producing both existing antibiotics and a wide range of new derivatives and analogs. In this paper, we review recent tools and strategies in metabolic engineering and synthetic biology for antibiotic discovery and the efficient production of antibiotics, their derivatives, and analogs, along with representative examples. Conclusion These metabolic engineering and synthetic biology strategies offer promising potential to revitalize the discovery and development of new antibiotics, providing renewed hope in humanity’s fight against MDR pathogenic bacteria.